Análise bardiniana de conteúdo do tema saúde nas questões de aplicação do Exame Nacional do Ensino Médio (ENEM) de 2009 a 2018 - Camila Gomes Xavier (2020)
Health education is a very important topic, especially during basic education, but it has been largely neglected. Considering the scarcity of studies on the health theme in the National High School Exam (ENEM), this research aims to investigate how this topic has been approached in the questions from 2009 to 2018. Using the content analysis methodology according to Bardin , we proceeded to the analysis of health issues regarding: 1) presence and validation of technical error; 2) relevance of the base text to the resolution of the questions; 3) relationship between the most addressed diseases in the national exam and those that cause the highest mortality according to the Ministry of Health; 4) contextualization of the questions. The results show that there is validation of the common sense, dispensability of base texts, incompatibility between the diseases that cause higher mortality in the country and the most addressed in the exam, besides the absence of contextualization in problem situations. Considering these aspects, it can be concluded that the exam questions need to be elaborated with more discretion, in order to be better contextualized. In addition, the questions should focus more on Biology content rather than on text interpretation with the goal to direct teaching towards meaningful and quality learning. .